Management information system modeling within the framework of the accreditation dashboard based on key performance indicators - Puspoko Ponco Ratno; Moh. Zainal Fanani (Institute of Computer Science (IOCS), 2023)
Accreditation is a quality guarantee or assessment of the suitability of study programs and higher education by the National Accreditation Board for Higher Education (BAN-PT). At the time this research was created, the Study Program at the Faculty of Tarbiyah was still processing and collecting reports manually, namely by using Ms. Excel and Ms. Word. This process still needs to be more effective regarding time and data accuracy. This research aims to produce prototype models of several accreditation criteria modules such as finance, facilities, infrastructure, and learning systems as part of SIMAKRE to make it easier for study programs to manage, process, and collect the data. The method used in this research is the Prototyping method using the web-based Laravel framework. Testing was carried out using the Black-box method. The test results of this system show that all functions run well according to user needs. The accreditation dashboard application aims to enhance efficiency in the accreditation process, especially ini Tarbiyah Faculty. This system can integrate data, show information in a style that is easy to grasp, and simplify the reporting process